Cormohipparion quinni (Mammalia, Equidae, Hipparionini) from the Middle Miocene (Late Barstovian) of Northern Costa Rica - Miller, Stephanie (2021)
For the first time the species Cormohipparion quinni Woodburne 1996 is recorded for the Late Barstovian of Central America and Costa Rica. This finding constitutes a new clue about the paleobiogeographical pattern of the Middle Miocene terrestrial mammals of North American and its incursion into the Neotropics of Southern Central America. This specimen represents the southernmost occurrence of this late Middle Miocene taxon at the North Hemisphere.